Demographic Factors Among HIV Confirmed Blood Donors from 2013 to 2021 in Shenzhen - Wang SX; Sun LY; Yu Q; Li T; Li R; Xu YP; Zeng JF (International Journal of General Medicine, 2023)
Song-Xing Wang,* Li-Yan Sun,* Qiong Yu, Tong Li, Ran Li, Yun-Ping Xu, Jin-Feng Zeng Shenzhen Blood Center, Shenzhen, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun-Ping Xu; Jin-Feng Zeng, Email yunpingxu1982@qq.com; zzengjf@163.comBackground: New HIV (Human immune deficiency virus) infections are continuously increasing in China and it remains a huge challenge to blood donation. As access to health services has affected by COVID-19 (Corona virus disease 2019) pandemic, a drop in new diagnoses (especially HIV) was observed worldwide.Methods: During 2013– 2021, 735,247 specimens from unpaid blood donors collected by Shenzhen Blood Center underwent ELISA (Enzyme -linked immunosorbent assay) and NAT (Nucleic acid test). Samples with reactivity results were sent to the Shenzhen Center for Disease Control and Prevention for WB (Western blot). All data were statistically analyzed by the Chi-Square test.Results: From 2013 to 2021, the prevalence of HIV among male blood donors was higher than in females (P < 0.01). During the COVID-19 pandemic, the prevalence of HIV among repeat blood donors decreased significantly compared to 2019 (P < 0.05), and the characteristics of blood donors changed in 2020 compared to 2019 and 2021.Conclusion: The high proportion of female blood donors would help prevent HIV from getting into the blood supply. The COVID-19 pandemic affected the demographics of blood donors as well as the prevalence of HIV among repeat blood donors. An increased number of repeat blood donors can help decrease the risk of HIV transfusion transmission during the epidemic.Keywords: COVID-19, Shenzhen, blood donors, HIV